2000
DOI: 10.1523/jneurosci.20-21-08021.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cell Migration and Aggregation in the Developing Telencephalon: Pulse-Labeling Chick Embryos with Bromodeoxyuridine

Abstract: Previous studies had concluded that the avian telencephalon develops according to an outside-in schedule of neurogenesis, with relatively little migration of young neuroblasts past older cells. These previous studies had, however, been based on the "cumulative labeling" method, which is less accurate than the "pulselabeling" method typically used in mammals. In the present study, we pulse-labeled chick embryos by injecting low doses of the thymidine analog bromodeoxyuridine (BrdU) directly into the circulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
72
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 54 publications
(77 reference statements)
18
72
0
Order By: Relevance
“…The embryos were sacrificed 0.5, 3, 6, 8-9 or 12 h after the initial application of BrdU. Previous work has shown that, unlike mammals, thymidine analogues are not rapidly metabolized in avian embryos (Striedter & Keefer 2000). Still, to ensure that high levels of unincorporated BrdU remained available within the egg, embryos sacrificed 6, 9 or 12 h after the initial BrdU application received additional doses of BrdU at 3 h intervals.…”
Section: Methodsmentioning
confidence: 99%
“…The embryos were sacrificed 0.5, 3, 6, 8-9 or 12 h after the initial application of BrdU. Previous work has shown that, unlike mammals, thymidine analogues are not rapidly metabolized in avian embryos (Striedter & Keefer 2000). Still, to ensure that high levels of unincorporated BrdU remained available within the egg, embryos sacrificed 6, 9 or 12 h after the initial BrdU application received additional doses of BrdU at 3 h intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, the clear‐cut inside‐first outside‐last development of the dorsal pallium has no counterpart in the avian embryonic brains (Tsai et al, 1981). With some exceptions (Striedter and Keefer, 2000), neuroblasts lack the ability to advance through older settled neurons. Consequently, early‐born neurons in the adult pallium occupy outer positions of the telencephalon (closer to the meninges), whereas late‐born neurons locate inner pallial zones (closer to the ventricle).…”
Section: Organization Of the Avian Palliummentioning
confidence: 99%
“…Consequently, early‐born neurons in the adult pallium occupy outer positions of the telencephalon (closer to the meninges), whereas late‐born neurons locate inner pallial zones (closer to the ventricle). In the developing hyperpallium of chickens, however, a clear pattern cannot be defined because early‐, mid‐, and late‐born neurons intermingle and show an apparently random distribution (Striedter and Keefer, 2000). In contrast, the pallium in quail develops roughly in an outside‐first inside‐last fashion; the cells born at early stages are distributed in both superficial and deep zones of the pallium, whereas those born at later stages are located specifically deeply in the pallium (Nomura et al, 2008).…”
Section: Organization Of the Avian Palliummentioning
confidence: 99%
See 2 more Smart Citations